Pengaruh Kepemimpinan dan Konflik Terhadap Prestasi Kerja Pegawai Dinas Pendidikan Kabupaten Tangerang Banten - Aan Angsori; Rugaiyah -; Matin - (Peneliti.net, 2018)
This study aims to obtain data, facts, and information about the influence of leadership and work performance conflict. This study uses survey research methods using quantitative-causal using path analysis. This mapping is carried out to analyze the relationship between variables with the aim to make direct or indirect relations of exogenous variables to endogenous variables. Based on the results of the research and discussion that have been described in the previous chapter, in the research on the Effect of Leadership and Conflict on Employee Performance of the Tanggerang District Education Office, it was concluded: (1) Direct positive leadership towards Job Performance. That is, effective leadership results in an increase in the work performance of employees of the Tanggerang District Education Office. (2) Negative direct conflict with Work Performance. That is, a decrease in work conflict Increases Job Performance of the Staff of the Tanggerang District Education Office. (3) Leadership has a direct negative effect on conflict. That is, effective leadership leads to a decline in the status of employees of the Tanggerang District Education Office. Thus, based on the results of these studies, it can be concluded that the Work Performance of the District Education Office of Tanggerang District is by conflict and conflict